AKTIVITAS STIMULASI KOMPONEN BIOAKTIF RIMPANG JAHE (Zingiber officinale Roscoe) PADA SEL LIMFOSIT B MANUSIA SECARA IN VITRO [Effects of Bioactive Compounds of Ginger (Zingiber officinale Roscoe) Root on B Cell Lymphocyte Function using In Vitro System - . Tejasari; Fransiska R Zakaria; Dondin Sajuthi (Jurnal Teknologi dan Industri Pangan, 2002)
The effect of two fractions of oleoresin compounds from ginger root on lymphocyte function were studied by observing B cell proliferations, which were  measured by the incorporation of 3H-thymidine during cell incubation. The doses of oleoresin compounds and its two fractions tested were 50,100, 150, and 200 mg per ml. Lymphocyte from human peripheral blood were isolated using ficoll density gradient technique, and cultured  in the presence of the compounds in RPMI-1640 medium for 4 days, with or without the addition of 3 mM paraquat as the oxidizing agent.  The results showed that the effects of oleoresin and its two fractions depended on its doses. Oleoresin and its two fractions increased B cell proliferation with  the highest activity of 456 percent at low dose of 50 mg per ml. These result showed a positive effect of oleoresin compound and its two fractions on B cell functions  at low doses. It indicated that bioactive compounds of ginger root at low  concentration have  positive effects on humoral immune response and this supports the traditional belief that ginger increases body resistance to common cold.